The Addition of Pharmacological Treatment to Physiotherapy in Pain Reduction of TMD-myalgia Patients - Carolina Marpaung; Hasti Parvaneh (Scientific Dental Journal, 2018)
Background: Myalgia is the most common cause of Temporomandibular Disorders (TMDs) pain, which has a dull and mild character. In some patients with high somatization, it can present itself as severe pain, which can complicate the treatment. Additional pharmacological treatment may thus be needed. Case Report: Two female patients came with similar symptoms but different pain intensities. The first patient had a high intensity of pain, which became severe during examination. The second patient had more complaints but showed typical symptoms of myalgia. Both received physiotherapy sessions, but for the first patient, we added analgesics to help the patient endure physiotherapy. Conclusion: Additional pharmacological treatments, especially analgesics, can be used in helping myalgia patients with high somatization to undergo physiotherapy.